PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM PERUMAHAN DAN ESDM DAERAH ISTIMEWA YOGYAKARTA - Achmad Mukhlisin; Ani Muttaqiyathun (Jurnal Fokus Manajemen Bisnis, 2017)
The purpose of this study was to determine the effect of the work environment andwork discipline on employee performance in the Public Works, Housing agency and ESDM DIY both partially and simultaneously (together). The population in this study amounted to 391 employees 198 samples were then taken using a sampling technique the sample is Simple Random Sampling with the Slovin formula. The type of data is data primary and data collection techniques using questionnaires that have been first tested with a test of validity and reliability. Analysis technique the data is multiple linear regression, t test, f test, and determination test. Based on the results of the analysis with statistical tools SPSS V 20 can be used it was concluded that the work environment (X1) and work discipline (X2) variables are good partially (singly) or simultaneously (together) influential significant impact on employee performance (Y) at the Department of Public Works, Housing and ESDM DIY.